Heparin-Induced Thrombocytopenia and Thrombosis: Preventing your Thrombolysis Practice from Taking a HITT - Wannamaker, Eric; Kondo, Kimi; Johnson, D. Thor (Seminars in Interventional Radiology, 2017)
Heparin-induced thrombocytopenia and thrombosis (HITT) is an under-recognized cause of deep venous thrombosis treatment failure and of complications during catheter-directed thrombolysis. After a review of HITT pathophysiology, diagnosis, and management, three different cases are presented in this article. Each case highlights subtleties and challenges of HITT diagnosis and management. An example of a practical approach to the diagnosis of HITT is presented.
Keywords: HITT; venous thrombosis; catheter-directed thrombolysis; interventional radiology; hypercoagulability workup